2021
DOI: 10.1088/2632-959x/abf8c2
|View full text |Cite
|
Sign up to set email alerts
|

Theories and models of supercapacitors with recent advancements: impact and interpretations

Abstract: Supercapacitors provide remarkable eco-friendly advancement in energy conversion and storage with a huge potential to control the future economy of the entire world. Currently, industries focus on the design and engineering aspects of supercapacitors with high performance (high energy), flexibility (by the use of composite polymer based electrolytes), high voltage (ionic liquid) and low cost. The paper reviews the modelling techniques like Empirical modelling, Dissipation transmission line models, Continuum mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 148 publications
0
16
0
Order By: Relevance
“…An EDLC comprises two electrolyte-soaked electrodes (made of porous carbon), which are separated by a thin separator. It stores energy through the formation of a nonfaradic electrical double layer (EDL) in the electrode and electrolyte interface through reversible ion adsorption onto the carbon surface. , This arrangement of electrical double-layer pairs separates the countercharges, thereby inducing capacitance between the electrodes. This type of charge-storage mechanism does not involve any faradaic (redox) reaction.…”
Section: Coal-derived Activated Carbon For Electrochemical Energy Sto...mentioning
confidence: 99%
“…An EDLC comprises two electrolyte-soaked electrodes (made of porous carbon), which are separated by a thin separator. It stores energy through the formation of a nonfaradic electrical double layer (EDL) in the electrode and electrolyte interface through reversible ion adsorption onto the carbon surface. , This arrangement of electrical double-layer pairs separates the countercharges, thereby inducing capacitance between the electrodes. This type of charge-storage mechanism does not involve any faradaic (redox) reaction.…”
Section: Coal-derived Activated Carbon For Electrochemical Energy Sto...mentioning
confidence: 99%
“…It is experimentally challenging to analyze the Stern-layer and diffuse-layer capacitance individually. Various numerical simulations have been done to study the behavior of EDLC. Conway and Pell evaluated the effect of porosity and distribution of interconnected capacitive and Ohmic elements on the behavior of electrochemical capacitors . Yoon et al analyzed the performance of thicker porous electrodes by simulating EDLC using transmission models. , Kaus et al have modeled a complex electrical model to account for the redistribution of ions in supercapacitors .…”
Section: Introductionmentioning
confidence: 99%
“…Metal oxides or conducting polymers like polyaniline or polypyrrole can be used as cathode materials. The EDLC//battery-type hybrid supercapacitor is another type [ 13 ], which uses metal oxides and hydroxides as the cathode materials and carbon materials as an anode.…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical behavior of carbon nanohorns/polyaniline (PANI)/PPy composites was examined by Chang et al [ 13 , 23 ], who found that they had outstanding cycling stability after 5000 cycles and a specific capacitance of 762 F∙g −1 at 5 m∙Vs −1 . For the PPy materials, Jiang et al employed CNT as a reinforcing component to lessen swelling and shrinkage throughout the doping and dedoping procedures.…”
Section: Introductionmentioning
confidence: 99%